Młode pokolenie w kulturze imagologicznej – wyzwania i zagrożenia rozwojowe - Wysocka, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Autorka w artykule przedstawia podstawowe problemy doświadczane przez młodzież w kulturze imagologicznej. Wskazuje główne trendy w rozwoju młodego pokolenia determinowane oddziaływaniem nowych technologii komunikacyjno-informacyjnych (TIK). Pokazuje główne źródła i mechanizmy wynikające z oddziaływań kultury obrazu oraz konsekwencje dla rozwoju młodego pokolenia. Artykuł jest próbą analizy świata życia młodego pokolenia w warunkach stworzonych przez nowe media.

In this article, the author presents the basic problems experienced by young people in the imaglogical culture. She indicates the main trends in the development of the young generation determined by the influence of new communication and information technologies (ICT). She indicates the main sources and mechanisms resulting from the impact of image culture and its consequences for the new generation’s development. This article is an attempt to analyze the lifeworld of the young generation in conditions created by new media.
The young generation in the imagological culture – developmental challenges and threats
Keywords: kultura imagologiczna; kultura obrazu; kultura słowa; młode pokolenie; świat życia młodzieży; zagrożenia i wyzwania rozwojowe; nowe media; imagological culture; image culture; word culture; young generation; the world of youth; developmental challenges and threats; new media